2013
DOI: 10.1177/2050157913476706
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone usage as an indicator of solidarity: Israelis at war in 2006 and 2009

Abstract: This study presents a secondary analysis of real-time data of mobile phone usage in Israel during two recent wars – with the Lebanese Hezbollah in 2006 and with the Palestinian Hamas in Gaza in 2008/9. The data, provided by Cellcom Israel, the country’s largest mobile operator, enabled an analysis of real behavior patterns rather than relying on memories of people who may have been under stress or traumatized during the hostilities, hence unable to accurately recollect this information later on. During both wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The entry of new media into our lives has gained broad scholarly interest in research on the coverage of wars and other crisis situations (Bennett, 2013;Lev-On, 2012;Meraz, 2006;Schejter and Cohen, 2013;Wall, 2005;Wolfsfeld, Segev and Sheafer, 2013). The premise is that, given the unique features of new media (as discussed below), the balance of power in the arena of political communication must be reassessed.…”
Section: War and Crisis In The Age Of New Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The entry of new media into our lives has gained broad scholarly interest in research on the coverage of wars and other crisis situations (Bennett, 2013;Lev-On, 2012;Meraz, 2006;Schejter and Cohen, 2013;Wall, 2005;Wolfsfeld, Segev and Sheafer, 2013). The premise is that, given the unique features of new media (as discussed below), the balance of power in the arena of political communication must be reassessed.…”
Section: War and Crisis In The Age Of New Mediamentioning
confidence: 99%
“…Shejter and Cohen (2013) evaluated the use of cell phones among Israelis during the Second Lebanon War (2006) and Operation 'Pillar of Defense' in the Gaza District in 2009. The researchers observed that, during these periods, the use of cell phones increased as a result of their most elementary component -their mobility -which made them usable at all times and everywhere.…”
Section: War and Crisis In The Age Of New Mediamentioning
confidence: 99%